Co-combustion of oil palm trunk biocoal/sub-bituminous coal fuel blends - Nudri, Nadly Aizat; Wan Abdul Karim Ghani, Wan Azlina; Bachmann, Robert Thomas; Baharudin, B. T. Hang Tuah; Ng, Denny K. S.; Md Said, Mohamad Syazarudin (Elsevier, 2021)
Biomass is a promising alternative for the reduction of global dependency on fossil fuels. However, there are some issues with the direct application of raw biomass such as high moisture content, low heating value, and poor grindability. To alleviate the problems, biomass-derived biocoal is introduced and utilised as fuel in power plants. Oil palm trunk biocoal (OPTC) is produced from pyrolysis of oil palm trunk biomass (OPTB) in a top-lit, updraft reactor at a constant air flowrate of 4.63 L/min and maximum temperature of 550 °C. OPTC is co-combusted at temperatures between 600 and 900 °C with sub-bituminous coal (SBC). Pollutant emission and ash production from combustion of fuel blends containing 20% and 50% biocoal are analysed and compared with pure SBC, OPTB and OPTC. NOx and SO2 emission profiles from all tested fuel blends are well below the limits imposed under Environmental Quality (Clean Air) Regulation 2014 of 296 and 190 ppm respectively. Response surface methodology (RSM) analysis indicates that the operation of combustion is optimised with 92.16% efficiency at 774 °C and air flowrate of 16.6 SCFH to emit 16.38% CO2, and the findings are validated against experimental results. The optimised combustion process produces ash with 67.9% silicon compounds.